1996
DOI: 10.1073/pnas.93.26.15254
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and germ cell parasitism in a colonial ascidian: Possible role for a highly polymorphic allorecognition system

Abstract: Here we demonstrate in laboratory and field experiments that both somatic cell and (more importantly) germ-line parasitism are a common occurrence in fused chimeras. These experiments support the tenet in Buss's hypothesis that germ cell and somatic cell parasitism can occur in fused chimeras and that a somatic appearance may mask the winner of a gametic war. They also provide an interesting challenge to develop formulas that describe the inheritance of competing germ lines rather than competing individuals. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 28 publications
5
108
0
Order By: Relevance
“…When DNA sequence allelic markers could be developed, we found that itinerant somatic and germline stem cells could move from colony zooid to other colony zooid, could participate in organogenesis, and later in the growing season could invade the incipient ovary and testis forming in every individual in the colony (181,182). Amazingly, Doug Stoner, Buki Rinkevich, and I showed that there were competitions between stem cell clones, the most dramatic at the level of formation of the germline stem cells, as measured by allelic polymorphisms shown in sperm and eggs (181,182).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 99%
See 1 more Smart Citation
“…When DNA sequence allelic markers could be developed, we found that itinerant somatic and germline stem cells could move from colony zooid to other colony zooid, could participate in organogenesis, and later in the growing season could invade the incipient ovary and testis forming in every individual in the colony (181,182). Amazingly, Doug Stoner, Buki Rinkevich, and I showed that there were competitions between stem cell clones, the most dramatic at the level of formation of the germline stem cells, as measured by allelic polymorphisms shown in sperm and eggs (181,182).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 99%
“…Amazingly, Doug Stoner, Buki Rinkevich, and I showed that there were competitions between stem cell clones, the most dramatic at the level of formation of the germline stem cells, as measured by allelic polymorphisms shown in sperm and eggs (181,182). There could be tens of genotype A colony individuals naturally parabiosed with tens of colony B, but in all reproductive organs we found that only colony A would be the next generation's germline (181,182). This winner-loser outcome was independent of colony size and was heritable on repeats in both asexual and sexual reproductive inheritance (181).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 99%
“…Although they must share at least one allele at this locus, they may be genetically different, and thus exploitation can occur (Stoner & Weissman, 1996). This can occur either by one clone totally dominating the other, often because it was older (Rinkevich et al, 1993), or by one invading the germ line of the other (Stoner & Weissman, 1996).…”
Section: Dominance Hierarchies In Other Systemsmentioning
confidence: 99%
“…Lastly, one puzzling phenomenon in these studies is that, whereas fused partners rarely maintain stability at the level of the colony, the eliminated partner may still persist, but at the level of the cell lineage (8,9). Those cells that escape allogeneic resorption may even parasitize the nonresorbed partner.…”
Section: Significancementioning
confidence: 99%
“…One chimeric partner is often eliminated in a process of allogeneic resorption, suggesting a break in immunological nonreactivity. Moreover, the eliminated partner may still persist, and even parasitize the nonresorbed partner, but at the level of the cell lineage (8,9). Insight has been gained into fusion-partner resorption from observational studies showing physical similarities with the developmental period known as "takeover," or blastogenic stage D (4, 10).…”
mentioning
confidence: 99%